2017
DOI: 10.1097/md.0000000000007376
|View full text |Cite
|
Sign up to set email alerts
|

The analgesic efficacy of oxycodone hydrochloride versus fentanyl during outpatient artificial abortion operation

Abstract: Background:Problems like body movement, respiratory depression, and complained of pain are still common phenomenon in outpatient artificial abortion general anesthesia. Oxycodone hydrochloride is a semisynthetic opioid and has a good therapeutic effect on visceral pain. We hypothesize that oxycodone hydrochloride would be superior to fentanyl in outpatient artificial abortion surgery.Methods:In this clinical trial 149 American Society of Anesthesiologists (ASA) I or II female outpatients scheduled for elective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 13 publications
1
14
1
Order By: Relevance
“…This concept was confirmed by other studies. Xie et al showed that patients receiving higher dose of oxycodone exhibited more delayed awakening and more drowsiness (higher RSS score) comparing to fentanyl [25]. However, different from our results, they found higher incidence of intraoperative respiratory depression and hypoxia in the fentanyl group [25].…”
Section: Discussioncontrasting
confidence: 99%
“…This concept was confirmed by other studies. Xie et al showed that patients receiving higher dose of oxycodone exhibited more delayed awakening and more drowsiness (higher RSS score) comparing to fentanyl [25]. However, different from our results, they found higher incidence of intraoperative respiratory depression and hypoxia in the fentanyl group [25].…”
Section: Discussioncontrasting
confidence: 99%
“…11,17 Opioids, the most commonly used type of analgesics for PCIA, have a clinical limitation because of side effects such as respiratory depression. 18 Many studies have investigated the effects of oxycodone for postoperative analgesia, 2,16,[19][20][21][22][23] however it is still controversial whether oxycodone can provide better transition analgesia and PCIA after gynecological tumors surgery under general anesthesia when compared with sufentanil. In our preliminary study, sufentanil PCIA without background infusion was applied; however, the intervals between bonus analgesia were too short (approximately 1 hour), which severely interfered patients' recovery and rest especially in the evening.…”
Section: Discussionmentioning
confidence: 99%
“…Action of the anesthetic drugs may be explained as follows: (1) inhibitory effect of sufentanil with μ receptor typical respiration can produce synergistic effect with propofol. Oxycodone produces analgesia by μ and κ receptors inhibiting the respiration itself, may be light, and does not significantly increase the propofol respiratory inhibition; 8 (2) sufentanil group may not provide enough inhibition of stress response of the airway, causing cough and airway spasm, checking the bronchoscopic placement, which in turn may result in a decline in ventilation and reduce SpO 2 . In addition, oxycodone has a good analgesic effect.…”
Section: Comparison Of Vital Signs In Patients Undergoing Surgerymentioning
confidence: 99%